2020
DOI: 10.1007/s00217-020-03633-6
|View full text |Cite
|
Sign up to set email alerts
|

Determination of FODMAP contents of common wheat and rye breads and the effects of processing on the final contents

Abstract: The benefits of a diet, low in fermentable oligo-, di- and monosaccharides and polyols (FODMAP) for patients suffering from irritable bowel syndrome (IBS) has been well established. Thus, the exact knowledge of the amount and composition of FODMAPs in foods is of vital importance for these patients. This study investigated the possibilities of FODMAP reduction by adjusting the processing parameters, which are feasible in practise, while still producing marketable breads. Therefore, the impact of prolonged proo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 34 publications
2
26
1
Order By: Relevance
“…In the case of wheat flour, the results obtained are similar to those reported by Schmidt et al [ 40 ], who studied the total carbohydrate content of wheat flour and rye to know exactly these compounds, with an important role in feeding people with irritable bowel syndrome. In the case of the study by Manoharlal et al [ 41 ] for Indian wheat flour, the results were lower than those reported by us.…”
Section: Resultssupporting
confidence: 86%
“…In the case of wheat flour, the results obtained are similar to those reported by Schmidt et al [ 40 ], who studied the total carbohydrate content of wheat flour and rye to know exactly these compounds, with an important role in feeding people with irritable bowel syndrome. In the case of the study by Manoharlal et al [ 41 ] for Indian wheat flour, the results were lower than those reported by us.…”
Section: Resultssupporting
confidence: 86%
“…Free soluble sugars were determined following the procedure described by Schmidt and Sciurba [ 22 ] with some modifications. In brief, 1.00 ± 0.01 g of sample was combined with 2.0 mL methanol and homogenized.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, the degradation of higher DP fructans is slower (Nilsson et al., 1987). Nonetheless, several studies reported that ∼40%−90% of the initially present fructans in wheat flour are degraded by yeast invertase during the bread‐making process (Gélinas et al., 2016; Knez et al., 2014; Laurent et al., 2020; Longin et al., 2020; Nilsson et al., 1987; Pejcz et al., 2019; Schmidt & Sciurba, 2021; Struyf, Laurent, Verspreet, et al., 2017; Struyf et al., 2018; Ziegler et al., 2016). For example, a white wheat bread made with flour that contains ∼1.2% fructans would require only ∼30% fructan degradation to result in a bread with fructan levels below the cutoff of 0.3 g/50 g bread (considering a moisture of 40% in bread).…”
Section: Strategies To Produce Low Fodmap Products and Their Current ...mentioning
confidence: 99%
“…These should be the benchmark for the targeted low FODMAP product development. Several studies investigated FODMAP reduction strategies, including the use of low FODMAP ingredients, and F I G U R E 1 Low fermentable oligosaccharides, disaccharides, monosaccharides, and polyol (FODMAP) diet and importance of nutritious functional low FODMAP products biotechnological FODMAP degradation through the action of purified enzymes, microbial enzymes during fermentation (specific yeast and lactic acid bacteria [LAB]), and activation of seed-endogenous enzymes during germination (Atzler et al, 2020(Atzler et al, , 2021bFraberger et al, 2018;Ispiryan, Kuktaite, et al, 2021;Li et al, 2020;Longin et al, 2020;Loponen & Gänzle, 2018;Loponen et al, 2017;Schmidt & Sciurba, 2021;Ziegler et al, 2016). The fundamental key principles of biotechnological FODMAP reduction have been recently reviewed by Nyyssölä et al (2020).…”
Section: Introductionmentioning
confidence: 99%